2005
DOI: 10.1093/cercor/bhi104
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Stress Induces Dendritic Spine Loss in the Rat Medial Prefrontal Cortex

Abstract: The prefrontal cortex (PFC) plays an important role in higher cognitive processes, and in the regulation of stress-induced hypothalamic-pituitary-adrenal (HPA) activity. Here we examined the effect of repeated restraint stress on dendritic spine number in the medial PFC. Rats were perfused after receiving 21 days of daily restraint stress, and intracellular iontophoretic injections of Lucifer Yellow were carried out in layer II/III pyramidal neurons in the anterior cingulate and prelimbic cortices. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
542
5
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 707 publications
(607 citation statements)
references
References 50 publications
35
542
5
8
Order By: Relevance
“…Parallel to the findings in the dentate gyrus, the PFC is now receiving increasing attention in preclinical research, especially because the involvement of this brain region in mood disorders is well documented (Drevets, 2000). Recent animal experiments show that chronic stress results in altered dendritic morphology, and reduced spine density in the mPFC, as has been shown in the hippocampal CA3 region (Cook and Wellman, 2004;Radley et al, 2004Radley et al, , 2006. Treatment with the synthetic glucocorticoid dexamethasone results in neuronal loss and atrophy in the mPFC as well as in the granule cell layer of the dentate gyrus (Cerqueira et al, 2005).…”
Section: Stress-induced Structural Changes and Their Potential Implicmentioning
confidence: 91%
“…Parallel to the findings in the dentate gyrus, the PFC is now receiving increasing attention in preclinical research, especially because the involvement of this brain region in mood disorders is well documented (Drevets, 2000). Recent animal experiments show that chronic stress results in altered dendritic morphology, and reduced spine density in the mPFC, as has been shown in the hippocampal CA3 region (Cook and Wellman, 2004;Radley et al, 2004Radley et al, , 2006. Treatment with the synthetic glucocorticoid dexamethasone results in neuronal loss and atrophy in the mPFC as well as in the granule cell layer of the dentate gyrus (Cerqueira et al, 2005).…”
Section: Stress-induced Structural Changes and Their Potential Implicmentioning
confidence: 91%
“…Interestingly, although the expression of PSA-NCAM seems to be exclusive of mPFC interneurons (Varea et al, 2005), all the structural changes reported in the mPFC were only described in pyramidal neurons (Radley et al, 2005). However, at least some of these principal neurons are surrounded by PSA-NCAM immunoreactive puncta that may correspond to synapses (Varea et al, 2005).…”
Section: Involvement Of Psa-ncam Expression In Mpfc Neuronal Structurmentioning
confidence: 97%
“…However, when the level of hormones remains elevated for a long period of time, the central nervous system can be cumulatively damaged by the exposure [10,16]. For instance, chronically elevated levels of cortisol can impair the development of the prefrontal cortex (PFC) [14], which has a large density of glucocorticoid receptors [17], causing dendrite retraction and a decline in the number of dendritic spines; both effects leading to an overall decrease in synaptic contacts [18][19][20].…”
Section: Introductionmentioning
confidence: 99%